Supercritical Carbon Dioxide Turbine Design and Arrangement Optimization - Li, Zhenya; Bian, Wenjie; Jiang, Li; Liu, Chuanliang; Shi, Jinyuan; Hao, Ning (Frontiers in Energy Research, 2022)
To achieve a supercritical CO2 cycle power generation system, a 25 MW supercritical CO2 turbine rotor and cylinder were designed. Then, two compact arrangement schemes were proposed in this paper for the optimization of a supercritical CO2 turbine rotor. In Scheme 1, the balance piston was arranged in the cooling gas section, which was more conducive to the arrangement of the dry gas seal. In Scheme II, the oil bearing was replaced by the gas bearing, and the dry gas seals at both ends of the turbine were installed outside the gas bearing, which was combined with the cooling gas section. The results suggest that the length of the rotor is reduced by 9% and 17% based on the above two schemes. The compact arrangement of the supercritical CO2 turbine can well reduce the shaft length of the turbine, which is beneficial to the structural design and operation of the supercritical CO2 turbine.